THE EFFECT OF JOB ENLARGEMENT ON JOB SATISFACTION WITH EMOTIONAL EXHAUSTION AS A MODERATION VARIABLE - I Wayan Aditya Tariana; Muhammad Risal Tawil; Kusuma Aghdi Rahwana; Dinesh Basti Farani; Suseno Hendratmoko (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This research is quantitative research with an explanatory approach. The data used in this research is primary data that researchers obtained from 500 Astra Daihatsu employees spread throughout Indonesia. The data used in this research contains 5 statements and 10 question items, namely strongly agree statement, agree statement, normal/average, disagree statement. These data were analyzed using smart PLS 4.0 tool